Experimental validation of the food disgust scale using olfactory stimuli. (April 2023) - Ammann, Jeanine; Egolf, Aisha; Nuessli Guth, Jeannette; Siegrist, Michael
Highlights: Our study is the first to validate the FDS short using olfactory stimuli. The disgusting odours were significantly correlated with the FDS short. Disgust reaction depends on the sensory channel used for the disgust stimulus. Abstract: Individual disgust reactions can be elicited through different types of sensory stimuli. Most well-known scales measuring disgust are text-based, thus more cognitive stimuli. This study aimed to validate the food disgust scale using olfactory stimuli related to food. For this, 150 participants were invited to our lab to rate different odours for the level of disgust evoked. Exploratory factor analysis (principal axis factoring) revealed two factors. The seven more disgusting items loaded on a first factor, whereas the two less disgusting items loaded on a second factor. The seven items loading on Factor 1 had acceptable reliability (Cronbach's α = 0.73, McDonald's Ω = 0.72). Further, Factor Score 1 was significantly correlated with the FDS short, a food disgust sensitivity questionnaire ( r  = 0.40, p  <.001). We conclude that food disgust sensitivity can help predict individuals' odour perception and our data support the incremental validity of the FDS short. Our study is the first to validate the FDS short using olfactory stimuli. Finally, our study indicates that there is significant potential for the creation of a food disgust odour scale.